First plant cell atlas workshop report. (15th October 2020) - Rice, Selena; Fryer, Emily; Ghosh Jha, Suryatapa; Malkovskiy, Andrey; Meyer, Heather; Thomas, Jason; Weizbauer, Renee; Zhao, Kangmei; Birnbaum, Kenneth; Ehrhardt, David; Wang, Zhiyong; Rhee, Seung Y.; et al.
Abstract: The societal challenges posed by a growing human population and climate change necessitate technical advances in plant science. Plant research makes vital contributions to society by advancing technologies that improve agricultural food production, biological energy capture and conversion, and human health. However, the plant biology community lacks a comprehensive understanding of molecular machinery, including their locations within cells, distributions and variations among different cell types, and real‐time dynamics. Fortunately, rapid advances in molecular methods, imaging, proteomics, and metabolomics made in the last decade afford unprecedented opportunities to develop a molecular‐level map of plant cells with high temporal and spatial resolution. The Plant Cell Atlas (PCA) initiative aims to generate a resource that will provide fresh insight into poorly understood aspects of plant cell structure and organization and enable the discovery of new cellular compartments and features. The PCA will be a community resource (www.plantcellatlas.org/ ) that describes the state of various plant cell types and integrates high‐resolution spatio‐temporal information of nucleic acids, proteins, and metabolites within plant cells. This first PCA initiative workshop convened scientists passionate about developing a comprehensive PCA to brainstorm about the state of the field, recent advances, the development of tools, and the future directions of this initiative. The workshop featured invited talks to share initial data, along with broader ideas for the PCA. Additionally, breakout sessions were organized around topics including the conceptual goals of the PCA, technical challenges, and community wants and needs. These activities connected scientists with diverse expertise and sparked important discussions about how to leverage and extend leading‐edge technologies and develop new techniques. A major outcome of the workshop was that the community wishes to redefine concepts of plant cell types and tissues quantitatively. A long‐term goal is to delineate all molecules within the cell at high spatio‐temporal resolution, obtain information about interacting molecular networks, and identify the contribution of these networks to development of the organism as a whole. As a first step, we wish to create comprehensive cellular and subcellular biomolecular maps of transcripts, proteins, and metabolites, track the dynamic interactions of these molecules intra‐ and intercellularly, discern complete states and transitions of specialized cell types, and integrate these disparate data points to generate testable models of cellular function. Ultimately, the PCA initiative will have a substantial positive impact by empowering a broad, diverse group of scientists to forge exciting paths in the field of plant science, facilitating connections with interested stakeholders beyond the scientific community, and enabling new agricultural technologies for a sustainable future.